The nature of the feast: commensality and the politics of consumption in Viking Age and Early Medieval Northern Europe. Issue 5 (20th October 2018) - Mainland, Ingrid; Batey, Colleen
ABSTRACT: In Early Medieval Northern Europe, food was more than mere sustenance. Rather, dietary choices were used to define and manipulate identity and shape power politics. Using the Norse Earldom of Orkney as a case study and commensality as an analytical framework, the authors explore how the archaeology of food, and in particular zooarchaeological evidence, can be used alongside near contemporary historical sources to better understand the political and social role of food, as well as the likely scale and impact of commensal activities on farming economies and environments in the Medieval North Atlantic. They argue that feasting and, by extension, the mechanisms by which preferentially consumed foodstuffs were grown, procured and processed, would have had a transformative impact on Norse society at diverse scales, from enabling individuals to participate in social negotiations to driving local and regional economies.